Pengaruh Resiliensi, Career Path Dan Employee Skill Terhadap Employee Performance Pada PDAM Kota Malang - Nofelinda Jesika Mayangsari; Pardiman Pardiman; Restu Millaningtyas (E-JRM : Elektronik Jurnal Riset Manajemen, 2021)
Abstract Employee performance both in quality and quantity enables the vision, mission and goals of the organization to be achieved. This test aims to test the extent of the influence of resilience, career path and employee skills on employee performance at PDAM Malang City. This type of research uses a quantitative approach. From the results of this study, the following results were obtained: (1) Simultaneously, the variable resilience, career path, and employee skill had a significant positive effect on employee performance. (2) partially, the resilience variable has a significant positive effect on employee performance. (3) the career path variable has a significant positive effect on employee performance. (4) employee skill variable has a significant positive effect on employee performance. This means that the higher the level of resilience, career path, and employee skills, the higher the employee performance. On the other hand, the lower the level of resilience, career path, and employee skills, the lower the employee performance. Keywords : Resiliensi, Career Path, Employee Skill, Employee Performance